Knowledge, Attitudes, And Home Conditions Among Tuberculosis Patients at Kamonji Public Health Center, Palu, Indonesia - Maryam Maryam; Rini Yulianti (Poltekkes Kemenkes Palu, 2026)
Background: Tuberculosis remains a major public health problem in Indonesia. Beyond clinical management, community knowledge, attitudes, and household physical conditions are important entry points for prevention because transmission often occurs in close indoor settings. This study described the knowledge, attitudes, and physical home environment of tuberculosis patients in the working area of Kamonji Public Health Center. Methods: This quantitative descriptive study was conducted in June 2024 in the working area of Kamonji Public Health Center, Palu Barat District. The study population consisted of 110 tuberculosis patients, and 52 respondents were included based on Slovin's sample size calculation with a 10% margin of error. Data were collected using a questionnaire for knowledge and attitudes, and an observation checklist for home lighting, ventilation, and humidity. Data were analyzed descriptively using frequencies and percentages. Results: Most respondents were aged 19-40 years (40.4%), male (67.3%), and worked as private employees (38.5%). Good knowledge was found in 39 respondents (75.0%), while 37 respondents (71.2%) had a positive attitude. Regarding home physical conditions, 35 houses (67.3%) met lighting standards, 30 houses (57.7%) met ventilation standards, and 33 houses (63.5%) met humidity standards. The largest environmental gap was ventilation, with 22 houses (42.3%) failing to meet the standard. Conclusion: Most tuberculosis patients in the Kamonji Public Health Center area had good knowledge and positive attitudes, and most houses met the observed physical environmental standards. However, inadequate ventilation remained common and should be prioritized in home-based environmental health counseling, routine home visits, and community tuberculosis prevention activities.